Hepatitis B Virus Transmission and Health-Care Workers: Prevention, Management, and Awareness toward the Disease - Bineeta Kashyap; Urvashi Tiwari; Anupam Prakash (Indian Journal of Medical Specialities)
The risk of transmission of hepatitis B, a global communicable disease, has become a matter of concern in recent years. Health-care delivery has the potential to transmit hepatitis B virus (HBV) and hepatitis C virus to both health-care workers (HCWs) and patients. The risk of transmission is most clearly related to the frequency of exposure or the extent of direct contact with human blood and body fluids. Health care must be provided with the best practice of safety and standards of care. Adherence to recommended improved safety devices, standard precautions, and fundamental infection-control practices is a must to prevent transmission of blood-borne pathogens. Long-term treatment with the goal of clearance of HBV is often required. Safe and effective hepatitis B vaccines along with postexposure prophylaxis with hepatitis B vaccination alone or in combination with HBV immunoglobulin have been available, the impact of which has been reported in several countries in preventing HBV transmission among HCWs.